STRUCTURE AND COMPOSITION OF WOODY VEGETATION IN TWO IMPORTANT BIRD AREAS IN SOUTHERN ZIMBABWE - P. Gandiwa; E. Chinoitezvi; E. Gandiwa (Journal of Animal and Plant Sciences, 2013)
This study assessed the status of woody vegetation structure and composition in two Important Bird Areas (IBA) i.e. Manjinji Pan and Save-Runde Junction located in southeastern Zimbabwe. The objectives of this study were to: (i) determine the woody vegetation structure and composition of the study areas and (ii) find out any differences and similarities in woody vegetation between the two IBAs. Data about woody vegetation were collected from 40 randomly placed sample plots from both study areas. Tree density was higher in Manjinji Pan IBA (406.67 ± 16.86 trees ha-1) than Save-Runde Junction IBA (275.83 ± 17.62 trees ha-1). In contrast, Save-Runde Junction IBA had higher numbers of stems per plant (2.88 ± 0.22), species richness (59) and diversity (H′ = 3.28) than Manjinji Pan IBA: numbers of stems per plant (2.16 ± 0.12), species richness (43) and diversity (H′ = 2.90). No significant differences were recorded in woody plant height, shrub and dead plant densities. The findings suggest that several factors including fires, herbivory and human activities could be influencing the woody vegetation in the two IBAs. However, further research is suggested to better understand the drivers of woody vegetation variation in IBAs occurring in savanna ecosystems. It is recommended that species richness and diversity of woody plants should be maintained and invasive plant species controlled for the conservation of endemic and migratory avifauna.
Keywords: Important Bird Areas; savanna; woody vegetation; fire; herbivory; species richness; diversity